Development of a Basic Manipulative Movement Learning Model (Object control) Play Activity Based for Students Grade V Elementary School (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of the study is to produce a learning model with valid, practical, and effective criteria. This type of research is development research using the Borg And Gall model. The population is all grade V students of State Elementary School 18 West Freshwater, Padang Utara District, Padang City. The sample was 30 class V students. The sampling technique is total sampling. The model validation design is validated by 2 experts: motor and language and model practicality by 2 sports teachers, The data collection instrument consists of tests of validity, practicality and effectiveness. As well as data analysis techniques using descriptive qualitative and quantitative techniques. The validation results of the learning model were obtained on average by 81.2.% with valid categories. In practicality, the results were obtained that this learning model was practical or good for use with learning implementation results of 91.7% The results of the effectiveness test using the Manipulative Basic Motion learning model based on play activities showed that there was a difference between obtaining manipulative motion ability results before using the model and after using the learning model. It was concluded that the model is effective and can improve the results of manipulative motion abilities (control objects) in the learning of sports and health physical education in grade V of primary school.